Testing momentum effectfor the US market: From equity to option strategies - Julián R. Siri; Juan A. Serur; José P. Dapena (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2017)
Conventional financial theory considers ex-ante that risk, generally measured by the volatility, has to be appropriately rewarded by expected returns. In modern financial markets, there are countless quantitative and systematic strategies which may test and eventually lead to excess returns when quantified by these conventional stochastic measures. One of them is the momentum effect which denotes an ongoing movement of the prices of financial assets in a certain direction, for a determined time horizon. Colloquially, assets that have performed better in the past tend to do so in the future. The objective of this paper is to test the existence of excess returns from momentum strategies. To do the aforementioned, we test different selection criteria with diverse weighting schemes. Finally, we analyze how is the behavior of equity options on those underlying assets in order to establish a two-way strategy; first performing pure equity option strategies and then blending equity options with index options.
Keywords: C1; C3; N2; G11; 330; Momentum; four-factor model; asset pricing; option pricing; implied volatility; index options